Short Run and Long Run Relationships between Saudi Stocks - Eltahir, Yassin; Osman, Hussien Omer; Sallam, Osama Azmi; Klabi, Fethi (International Journal of Economics and Financial Issues, 2019)
The main objective of this study is to know whether short and long run relationships exist between stock values in the Saudi market. For that purpose, the authors extracted daily stock value data from five distinct Saudi economic sectors. Using modern statistical techniques through MGARCH (DVEC) and error correction models, the authors estimated the stock return variances and concluded that stock values are correlated. On this basis, stocks were found to be stable and safe and detained larger effects on the rest of stocks (Rajhi, banking sector), some were unstable (Bahri, the national shipping carrier), some have moderate effects (Etisalate, telecommunication) and others have no effects such as Almarai (Food industries) and Sabic (petrochemicals). Overall, this study concludes that the Saudi market is stable and safe. Keywords: Error Correction Model, M GARCH-VEC, Saudi Market JEL Classifications: C58, E44, G2 DOI: https://doi.org/10.32479/ijefi.7391